2016
DOI: 10.1016/j.jcma.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Ang-(1–7) inhibited mitochondrial fission in high-glucose-induced podocytes by upregulation of miR-30a and downregulation of Drp1 and p53

Abstract: Ang-(1-7) inhibited mitochondrial fission in HG-induced podocytes by upregulation of miR-30a and downregulation of Drp1 and p53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Drp1 overexpression has been widely reported in HG and diabetic conditions. Podocytes and glomerular mesangial cells grown in HG medium exhibit significant Drp1 upregulation and increased mitochondrial fission, which promote podocyte loss and compromise glomerular function, suggesting that elevated Drp1 plays a role in the pathogenesis of diabetic nephropathy [25][26][27]. In addition, Drp1 overexpression was observed in pancreatic β-islet cells grown in HG medium concomitant with increased mitochondrial fission, cytochrome c release, reduced mitochondrial membrane potential, caspase-3 activation, and reactive oxygen species (ROS) production [28].…”
Section: Introductionmentioning
confidence: 99%
“…Drp1 overexpression has been widely reported in HG and diabetic conditions. Podocytes and glomerular mesangial cells grown in HG medium exhibit significant Drp1 upregulation and increased mitochondrial fission, which promote podocyte loss and compromise glomerular function, suggesting that elevated Drp1 plays a role in the pathogenesis of diabetic nephropathy [25][26][27]. In addition, Drp1 overexpression was observed in pancreatic β-islet cells grown in HG medium concomitant with increased mitochondrial fission, cytochrome c release, reduced mitochondrial membrane potential, caspase-3 activation, and reactive oxygen species (ROS) production [28].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these findings, Ma et al [ 112 ] found that mice with genetic deletion of the AT2 receptor gene have (1) decreased cortical ACE2 activity, Mas expression, and Ang-(1-7) levels in kidney tissue; (2) increased production of ACE, Ang II, and AT1 receptor in kidney cortex; (3) high BP, increased indices of kidney injury, and mesangial matrix expansion score; and (4) microalbuminuria. Ali et al [ 113 ] showed that AT2 and Mas receptors have molecular interactions, mainly concerning NO release and diuretic responses.…”
Section: Role Of Classical and Alternative Raas Axes In Pediatric Kidmentioning
confidence: 74%
“…In INS1 cells incubated with 20 mmol/l glucose, expression of proteins ( MFN1, MFN2, OPA1, FIS1 , and DRP1 ) is significantly reduced, with the greatest reduction for FIS1 (Schultz et al, 2016). High glucose induces an increase in DRP1 in podocytes (Ma et al, 2016). High glucose and high palmitate increase expression of FIS1 and p- DRP1/DRP1 and decrease expression of MFN2 (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%